2020
DOI: 10.3390/jcm9041172
|View full text |Cite
|
Sign up to set email alerts
|

Oral-Health-Related Quality of Life in Adult Patients with Rheumatic Diseases—A Systematic Review

Abstract: Objectives: The aim of this systematic review was to assess the oral-health-related quality of life (OHRQoL) of adult patients with rheumatic diseases. Material and Methods: A systematic literature search was performed, including clinical studies on adults (aged at least 18 years) with a verified diagnosis of rheumatic disease. Results: 26 out of 41 clinical studies including rheumatoid arthritis (RA, seven studies), systemic sclerosis (SSc, five), Sjögren syndrome (SS, eight), Behcet disease (BD, four), syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 51 publications
2
44
0
Order By: Relevance
“…Patients with severe chronic diseases or conditions, e.g., rheumatic diseases or hemodialysis show a reduced OHRQoL caused by their general disease burden including pain and impact on their daily life (15,28). Thereby, the OHIP-14 values for patients with respiratory diseases in this study were similar as for rheumatic diseased patients or individuals undergoing renal replacement therapy (15,28). Thus, the HRQoL impairment due to the general disease could be one reason for the reduced OHRQoL in this study; especially, severely diseased individuals with proceeded COPD, cystic fibrosis, and severe asthma are impaired in their everyday life and show affected HRQoL (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients with severe chronic diseases or conditions, e.g., rheumatic diseases or hemodialysis show a reduced OHRQoL caused by their general disease burden including pain and impact on their daily life (15,28). Thereby, the OHIP-14 values for patients with respiratory diseases in this study were similar as for rheumatic diseased patients or individuals undergoing renal replacement therapy (15,28). Thus, the HRQoL impairment due to the general disease could be one reason for the reduced OHRQoL in this study; especially, severely diseased individuals with proceeded COPD, cystic fibrosis, and severe asthma are impaired in their everyday life and show affected HRQoL (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…It is known that oral health can affect general HRQoL ( 26 ) and that reduced HRQoL can negatively affect OHRQoL ( 13 , 27 ). Patients with severe chronic diseases or conditions, e.g., rheumatic diseases or hemodialysis show a reduced OHRQoL caused by their general disease burden including pain and impact on their daily life ( 15 , 28 ). Thereby, the OHIP-14 values for patients with respiratory diseases in this study were similar as for rheumatic diseased patients or individuals undergoing renal replacement therapy ( 15 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SSc is associated with significant morbidity with variable outcomes 4 . A systematic review to assess the oral‐health‐related quality of life (OHRQoL) of adult patients with rheumatic diseases concluded that rheumatic diseases with oral involvement, such as SSc, has lower OHRQoL due to oral and psychosocial impairments compared to other rheumatic diseases 5 . A web‐based survey by Leader et al (2014) suggested approximately 50% of dentists ( n = 269) felt they might cause harm to SSc patients because of their insufficient knowledge of the disease 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the authors hypothesized a shared pathophysiology between the two diseases, based on a local and systemic proinflammatory environment and related oxidative stress. Finally, the third systematic review performed by Schmalz et al [ 15 ] evaluated the oral health-related quality of life in adults with different systemic rheumatic diseases. Thereby, 26 studies with six different rheumatic entities were included.…”
mentioning
confidence: 99%